Second form - Cox, Pamela (London ; Hodder childern books, 2019)
Darrell, Sally, Gwendoline, Mary Lou and all the girls are now in the second form, but they are as lively as ever. Mam'zelle Dupont is still trying to be strict, Alicia plays a trick with invisible chalk and Gwendoline and Daphne get into trouble
Keywords: English - Teenager Fiction Book